Photopyroelectric characteristics of Pr6O11 - ZnO ceramic composites. - Rizwan, Zahid; Mohd Ghazali, Mohd Sabri; Zakaria , Azmi (Academic Journals, 2011)
Characteristics of different Pr6O11 ceramic composites were studied using photopyroelectric spectroscopy. The amount of Pr6O11 in the composite was varied from 0.1 to 0.75 mol% at the sintering temperature of 1190 and 1270°C. It was found that optical energy band-gap (Eg) of the composite is reduced by increasing the amount of Pr6O11 in the composite at both sintering temperatures. However, the decrease in Eg was relatively less at a sintering temperature of 1270°C as compared to that of 1190°C. XRD analysis showed that all samples have two phases, that is ZnO and intergranular layers composed of Pr6O11 and few small peaks of Pr2O3. EDAX results further showed that the Pr6O11 and Pr2O3 were segregated in the grain boundaries. Maximum grain size of 5.85 μm and relative density of 94.5% were found in these ceramics at x = 0.1 and 0.5 mol%, respectively, for 1270°C sintering temperature.